2018
DOI: 10.1177/1534508418819797
|View full text |Cite
|
Sign up to set email alerts
|

Universal Screening Methods and Models: Diagnostic Accuracy of Reading Assessments

Abstract: Reading screening assessments help educators identify students who are at risk of reading and determine the need for intervention and supports. However, some schools screen and assess students more often than needed, and the additional information does not improve the accuracy of decisions. This may be especially true for students at the upper elementary grades who have already taken high-stakes tests. This exploratory study evaluated how accurately a variety of screening measures predicted performance on a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The extent to which CBM captures growth and responsiveness to instruction, relative to other measures, remains an important consideration in evaluating reading instruction for children with DS (Lemons & Fuchs, 2010). CBM is used as a universal screening and progress monitoring tool within school-wide multitiered systems of support (MTSS) frameworks designed to allocate educational resources through ongoing assessment (Van Meveren et al, 2020). A related use of CBM is data-based individualization (DBI; Fuchs et al, 2020).…”
mentioning
confidence: 99%
“…The extent to which CBM captures growth and responsiveness to instruction, relative to other measures, remains an important consideration in evaluating reading instruction for children with DS (Lemons & Fuchs, 2010). CBM is used as a universal screening and progress monitoring tool within school-wide multitiered systems of support (MTSS) frameworks designed to allocate educational resources through ongoing assessment (Van Meveren et al, 2020). A related use of CBM is data-based individualization (DBI; Fuchs et al, 2020).…”
mentioning
confidence: 99%
“…Based on the results from this study showing lack of sensitivity to growth and the lack of prior independent investigation of growth trajectories, the Math MAP needs additional evidence from Stage 2 research studies to be considered an effective, recommended progress monitoring tool. In terms of the Math MAP, there is also a need for additional Stage 1 studies, such as the ones completed for the Reading and Language Usage MAP tests (e.g., Ball & O'Connor, 2016; January & Ardoin, 2015; Klingbeil et al, 2017; VanMeveren et al, 2018). Further evidence would make a stronger case for the Math MAP, part of MAP Growth, as a screening and growth measure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ball and O'Connor (2016) found that the Reading and Language Usage MAP tests in combination with oral reading fluency and special education status, explained 68% of the variance in performance on the Wisconsin end‐of‐year assessment. Additionally, there is evidence for the MAP as the better predictor of performance, on the Minnesota state assessment, as compared to CBM, student growth, and previous state test scores (VanMeveren et al, 2018). Furthermore, the Reading MAP and reading CBM have concurrent validity for universal screening (January & Ardoin, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screeners used for educational decision-making should be brief, require few resources, and disrupt the educational routine as little as possible (Kilgus et al, 2013). Many schools already conduct reading screening three times each year to identify children who are at risk for reading difficulties and to improve student learning by targeting intervention so that students do not fall further behind their peers (VanMeveren et al, 2020). Next, we will discuss a commonly used reading screener and a relatively new one purportedly designed to screen for dyslexia.…”
Section: Screening Of Reading and Dyslexiamentioning
confidence: 99%